Improvement of Mechanical and Biological Properties of PLA/HNT Scaffolds Fabricated by Foam Injection Molding: Skin Layer Effect and Laser Texturing - Eryildiz, M.; Altan, M.; Odabas, S. (WALTER DE GRUYTER GMBH, 2021)
Polylactic acid (PLA) is one of the important materials for orthopedic regenerative engineering applications due to its biodegradability and biocompatibility. Nonetheless, PLA may show insufficient mechanical strength for some bone replace-ment applications. Halloysite nanotube (HNT) is one of the non-toxic, biocompatible reinforcement for improving me-chanical and biological properties of PLA for tissue engineer-ing applications. In this study, PLA/HNT scaffolds were pre-pared by chemical foam injection molding process. Laser surface texturing was applied on the skin layer of the injection molded scaffolds to enhance the cell viability and hydrophili-city of PLA. The effects of HNT concentration on cell mor-phology, mechanical and thermal properties, cell viability and biodegradation profile of the scaffolds were studied. The results demonstrated that cell viability increased by 43 % in PLA/HNT scaffolds compared to neat PLA. Hydrophilicity of the scaffolds that have thick skin layer was enhanced by the laser surface texturing in two different designs and conse-quently, cell viability increased about 16%. Surface rough-ness measurements and water contact angle measurements have verified this result.
Keywords: POLY(LACTIC ACID); NANOTUBE NANOCOMPOSITES; POROUS SCAFFOLDS; HALLOYSITE; BEHAVIOR; PLA; DEGRADATION; MORPHOLOGY; CRYSTALLIZATION; CRYSTALLINITY; Engineering; Polymer Science